Differential Autophagy Response in Men and Women After Muscle Damage - Luk, Hui-Ying; Appell, Casey; Levitt, Danielle E.; Jiwan, Nigel C.; Vingren, Jakob L. (Frontiers in Physiology, 2021)
Following muscle damage, autophagy is crucial for muscle regeneration. Hormones (e.g., testosterone, cortisol) regulate this process and sex differences in autophagic flux exist in the basal state. However, to date, no study has examined the effect of a transient hormonal response following eccentric exercise-induced muscle damage (EE) between untrained young men and women. Untrained men (n=8, 22±3yr) and women (n=8, 19±1yr) completed 2 sessions of 80 unilateral maximal eccentric knee extensions followed by either upper body resistance exercise (RE; designed to induce a hormonal response; EE+RE) or a time-matched rest period (20 min; EE+REST). Vastus lateralis biopsy samples were collected before (BL), and 12 h, and 24 h after RE/REST. Gene and protein expression levels of selective markers for autophagic initiation signaling, phagophore initiation, and elongation/sequestration were determined. Basal markers of autophagy were not different between sexes. For EE+RE, although initiation signaling (FOXO3) and autophagy-promoting (BECN1) genes were greater (p < 0.0001; 12.4-fold, p = 0.0010; 10.5-fold, respectively) for women than men, autophagic flux (LC3-II/LC3-I protein ratio) did not change for women and was lower (p < 0.0001 3.0-fold) than men. Furthermore, regardless of hormonal changes, LC3-I and LC3-II protein content decreased (p =0.0090; 0.547-fold, p = 0.0410; 0.307-fold, respectively) for men suggesting increased LC3-I lipidation and autophagosome degradation whereas LC3-I protein content increased (p =0.0360; 1.485-fold) for women suggesting decreased LC3-I lipidation. Collectively, our findings demonstrated basal autophagy was not different between men and women, did not change after EE alone, and was promoted with the acute hormonal increase after RE only in men but not in women. Thus, the autophagy response to moderate muscle damage is promoted by RE-induced hormonal changes in men only.